PENGARUH KAMPANYE PAJAK TERHADAP KESADARAN MASYARAKAT MELAPORKAN SURAT PEMBERITAHUAN TAHUNAN (SPT) : Survei Kepada Karyawan BPJS Kantor Wilayah Jakarta Timur - Dewi Sefiyani; Yayu Sriwartini (Universitas Nasional, 2020)
The purpose of this study is to determine whether there is an influence of tax campaigns on public awareness of reporting annual notification (SPT), to find out how much the value of campaign contributions to public awareness of reporting Annual Notification Letter (SPT). This study uses an explanatory survey method. The sample of this study amounted to 45 people by distributing questionnaires to employees of the Social Security Administration Agency (BPJS). Determination of sample size in research using the Yamane formula based on an error rate of 5%. The theory used in this research is Attribution Theory. The results showed that there was a significant effect on public awareness of reporting Annual Notification Letter (SPT), with a high level of relationship. The magnitude of the influence of the tax campaign by 43.6% on public awareness to report the Annual Notification Letter (SPT).